Investigation on Compressibility and Microstructure Evolution of Intact Loess at Different Wetting States - Jian, Tao; Kong, Lingwei; Bai, Wei; Sun, Zhiliang (Frontiers in Earth Science, 2022)
Loess is widely deposited in arid and semi-arid areas and is characterized by low dry density, developed pore space, and loose structure, which is not commensurate with high structural strength and shear strength in the dry state. Many natural phenomena and experimental results show that intact loess is very sensitive to the change of water content, and a slight increase in water content can cause a rapid reduction in strength. Abundant information is available in the literature for the collapsibility of loess. However, research on the evolution of loess compressibility during wetting, which is very helpful in understanding loess collapsible deformation caused by long-term irrigation, remains minimal. To this end, in this article, the evolution of the compressibility of intact loess at different wetting stages is investigated by oedometer tests, and microstructure and pore size distribution (PSD) were characterized on intact loess specimens at different water contents before and after oedometer tests by scanning electron microscope (SEM) and mercury intrusion porosimetry (MIP) methods. The results show that the compression index (Cc) and secondary compression index (Cα) of intact loess depend on water content and vertical stress and change abruptly when vertical stress exceeds yield stress. Cα/Cc values of intact loess are not constant, which increases with vertical stress to a peak and then gradually decreases to 0.025. Wetting and loading can cause damage to the microstructure of intact loess; specifically, loading leads to the collapse of the overhead structure and the transformation from a bimodal PSD into a unimodal PSD, and wetting intensifies the collapse of the microstructure to form a compacted interlocking structure and promotes the transformation of medium pores into small pores.